Learning Approach to Climate Change Education as a Framework for Sustainability Education: A Systematic Review of Literature - Luthfia, Syarifatul (IJCER (International Journal of Chemistry Education Research), 2025)
Earth's society is facing a complex problem, it is climate change. This phenomenon has caused significant impacts on human life, such as water crises, natural disasters, health problems, food shortages, and other socio-economic challenges. Educational must contributes to this important matter. Therefore, the development of a sustainable educational framework to address this issue is imperative. Education is a strategic field to influence individuals, particularly students to develop knowledge, skills, and the capacity to adapt and mitigate to climate change. Based the importance of sustainable education to face climate change problems, needed to study about the approach of climate change-related learning. The aim of this research is to gain an in-depth insight into the various approaches of Climate change Education (CCE) application in primary and secondary school. This study used a systematic literature review method to collect and analyse data from 28 articles relevant to the topic under study. So far, there hasn't conducted study about the approach climate change learning with SRL (Systematic Review of Literature) methode from 2015 to 2024 from diverse prespectives. Results of the study classified various of approaches, there are curriculum, professional development, learning model, interdicipliner, project, and community approach. This research shows that climate change education involves not only students and teachers but also the local community. The implications of the results of this study are useful for the development of climate change education as sustainability education.